Clinical monitoring of safety and functionality of a non-medicated patch for pain alleviation associated to dysmenorrhea - Mori, Michela Maria; Busoli Badiale, Silvia; Pastoris, Ornella; Bianchi, Fernando; Angelinetta, Marco Claudio (Acta Biomedica Atenei Parmensis, 2019)
FIT® Lady patch is an easy-to-use class I medical device, developed to relieve pain associate to menstrual period, without pharmacological substances. The patch is based on far infrared (FIR) electromagnetic waves reflection properties that normally are emitted from the body, as a consequence of body heat dispersion between the difference of cutaneous body and ambient temperature. Consequently, infrared (IR) waves are reflected and resorbed at cutaneous level and thermal energy again locally introduced leads to a better microcirculation. Although biological IR waves properties and mechanisms of action are extensively studied, there are still few references on patches based on FIR properties. The aim of this study was the evaluation of FIR technology applied to FIT® Lady patch thought to be used to alleviate pain associated to menstrual period (dysmenorrhea). The FIT® Lady patch medical device (active patch) was evaluated in comparison with a placebo patch, in order to assess its action in reducing pain related to menstrual period in 40 women patients enrolled according to specific inclusion/exclusion criteria. This study confirmed a good tolerability of the product, by demonstrating the ability to significantly reduce inconvenience and feeling of pain. The mineral that was responsible of the reflection activity (titanium dioxide), conveniently entrapped in a patch, was able to work without any active substances in contact with and absorbed from the skin.